183 The optimal SID lysine: crude protein ratio for maximal nitrogen efficiency in piglets. - Millet, S (J Anim Sci, 2018)
Lowering the crude protein (CP) level in the piglet diet reduces the risk of post-weaning diarrhea and nitrogen (N) excretion to the environment. The question remains at what point CP becomes limiting. Therefore 12 diets were formulated with 2 standardized ileal digestible (SID) lysine (LYS) levels (10 and 11 g SID LYS) and 6 CP levels (140, 150, 160, 170, 180, 190 g/kg) which were fed to piglets between 4 and 9 weeks of age in a 2 x 6 design with 6 pens of 6 animals per treatment. Serum urea levels were measured to assess N metabolism, with lower levels indicating a higher N efficiency. Linear plateau models could be fitted in function of the SID LYS:CP ratio. With 10 g SID LYS, serum urea decreased with decreasing CP levels down to a minimal level of 3.1 mg/dl at 63.9 g SID LYS/kg CP (156 g CP/kg). With 11 g SID LYS, serum urea decreased with decreasing CP levels to a minimum of 3.9 mg/dl at 63.3 g LYS/kg CP (174 g CP/kg). Over the 12 treatment groups, a breakpoint was calculated at 63.5 g SID LYS/kg CP, above which the protein breakdown was minimal and therefore N efficiency maximal. Both LYS and CP level affected daily gain and gain to feed (G:F). The breakpoint in G:F was at 60.6 and 62.5 g SID LYS/kg CP (165 and 175 g CP/kg) for pigs receiving 10 or 11 g SID LYS/kg, respectively. The results suggest that, apart from essential amino acids, the dietary profile of non-essential amino acids may be limiting performance. The ratio of 63.5 g SID LYS/kg CP may be a guideline/threshold value for maximizing the conversion of vegetal to animal protein in piglets.